2017
DOI: 10.1108/ara-12-2014-0128
|View full text |Cite
|
Sign up to set email alerts
|

Effect of audit and compensation committee membership overlap on audit fees

Abstract: Purpose Recent studies document that approximately two-thirds of sample firms have at least one audit committee member serving on their compensation committee (Liao and Hsu, 2013). Prior studies on overlap membership document that presence of audit committee members on compensation committee affects the reporting quality. Since auditors’ audit risk is affected by reporting quality. The purpose of this paper is to examine how the auditors perceive the overlap of audit and compensation committee members when pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 51 publications
4
23
0
Order By: Relevance
“…Our findings are robust to two alternative measures of financial reporting quality (i.e., earnings restatements and non-audit fees (NAF)) and are in line with the theoretical model by Laux and Laux (2009), who assume that overlapping memberships can be connected with an increased knowledge of pay-for-performance compensation and with a better position to analyse management's incentives for earnings management. Furthermore, our results are in line with Fernandez-Mendez et al (2017), Kalelkar (2017), Habib and Bhuiyan (2016) and Chandar et al (2012).…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our findings are robust to two alternative measures of financial reporting quality (i.e., earnings restatements and non-audit fees (NAF)) and are in line with the theoretical model by Laux and Laux (2009), who assume that overlapping memberships can be connected with an increased knowledge of pay-for-performance compensation and with a better position to analyse management's incentives for earnings management. Furthermore, our results are in line with Fernandez-Mendez et al (2017), Kalelkar (2017), Habib and Bhuiyan (2016) and Chandar et al (2012).…”
Section: Introductionsupporting
confidence: 89%
“…We have contributed to previous empirical studies by Fernandez-Mendez et al (2017), Kalelkar (2017), Habib and Bhuiyan (2016) and Chandar et al (2012) for the US, Spanish and Australian capital market, who also found a positive impact of OMAC on financial reporting quality. However, our results contrast the US findings by Liao and Hsu (2013) and Chang et al (2011), who found a negative impact of OMAC on financial reporting quality.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In particular, special committees should play an active role in governance to incentivise and supervise the CEO. Kalelkar [1], Collier and Gregory [2], Sultana et al [3], and Bajra andČadež [4] discovered that the supervision efforts of the audit committee can improve the quality of a company's financial reports and reduce financial risks. Ghafran and O'Sullivan [5] noted that an audit committee with a professional background can inhibit an agent's earnings manipulation behaviour.…”
Section: Introductionmentioning
confidence: 99%